Vortex dynamics of in-line twin synthetic jets in a laminar boundary layer - Wen, Xin (2015)
An experimental investigation is conducted on the vortices induced by twin synthetic jets (SJs) in line with a laminar boundary layer flow over a flat plate. The twin SJs operating at four different phase differences, i.e., Δϕ = 0°, 90°, 180°, and 270°, are visualized using a stereoscopic color dye visualization system and measured using a two-dimensional particle image velocimetry (PIV) system. It is found that depending on the phase difference of twin SJs, three types of vortex structures are produced. At Δϕ = 90°, the two hairpin vortices interact in a very constructive way in terms of the vortex size, strength, and celerity, forming one combined vortex . At Δϕ = 270°, the two individual hairpin vortices do not have much interaction, forming two completely separated hairpin vortices that behave like doubling the frequency of the single SJ case. At Δϕ = 0° and 180°, the two hairpin vortices produced by the twin SJ actuators are close enough, with the head of one hairpin vortex coupled with the legs of the other, forming partially interacting vortex structures. Quantitative analysis of the twin SJs is conducted, including the time histories of vortex circulation in the mid-span plane as well as a selected spanwise-wall-normal plane, and the influence of the twin SJs on the boundary layer flow filed. In addition, dynamic mode decomposition analysis of the PIV data is conducted to extract representative coherent structures. Through this study, a better understanding in the vortex dynamics associated with the interaction of in-line twin SJs in laminar boundary layers is achieved, which provides useful information for future SJ-array applications.